The Meaning of Verbal and Non Verbal Sign of “Insidious” Film Poster - Ida Ayu Putri Gita Ardiantari; Ni Putu Ghalih Diana Wati (Prodi Sastra Inggris Fakultas Bahasa Asing Universitas Mahasaraswati Denpasar, 2023)
This research is entitled 'The Meaning of Verbal and Non-Verbal Sign of Insidious Film Poster. This study aimed to find verbal and non-verbal signs on the Insidious film poster and explain the meaning of verbal and non-verbal signs in the Insidious film poster. Research data were taken from websites on the internet. The data source for this research were posters in the Insidious film series. The films is Insidious 2011, Insidious chapter 2 (2013), Insidious chapter 3 (2015). These verbal and non-verbal signs were analyzed by using the Semiotic theory of Roland Barthes (1967) about denotative and connotative meanings using qualitative analysis methods. It was found 5 verbal and 5 non-verbal signs on the Insidious 2011 poster, 3 verbal signs and 4 non-verbal signs on the Insidious chapter 2 poster, and 3 verbal signs and 3 non-verbal signs on the Insidious chapter 3 poster. Verbal signs are: title, actor name, tagline, character, and place of occurrence. Meanwhile, Non-verbal signs were also found in the film poster in the form of: Haunted house, boy, scared character.